(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
The seed oil of Annona salzmannii A. DC. was analyzed by GC-MS and 1 H qNMR, revealing a mixture of unsaturated (80.5%) and saturated (18.7%) fatty acids. Linoleic (45.3%) and oleic (33.5%) acid were the major unsaturated fatty acids identified, while palmitic acid (14.3%) was the major saturated fatty acid. The larvicidal effects of A. salzmannii seed oil were evaluated against third-instar larvae of Aedes aegypti (Linn.). The oil exhibited moderate larvicidal activity, with aLC50 of 569.77 ppm (95% CI = 408.11 to 825.88 ppm). However, when the cytotoxic effects of the oil were evaluated, no expressive antiproliferative effects were observed in tumor cell lines B16-F10 (mouse melanoma), HepG2 (human hepatocellular carcinoma), K562 (human chronic myelocytic leukemia), HL-60 (human promyelocytic leukemia), and non-tumor cell line PBMC (peripheral blood mononuclear cells), with IC50 values > 50 μg·mL-1. This is the first study to evaluate the chemical composition, larvicidal and cytotoxic activity of A. salzmannii seed oil.